Metaphysics of Consciousness The Indian Vedantic Perspective - Pradhan, Ramesh Chandra; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book explores the transition from the mind to the Supermind within the scope of an evolutionary metaphysics. The idea of Supermind has not been discussed so far in the mainstream philosophy of mind and consciousness. This book will give a new approach to the study of consciousness from the Indian Vedantic perspective which has introduced the idea of Supermind, especially in the works of Sri Aurobindo. The book also undertakes a sustained critique of the contemporary theories of mind which have promoted mostly a mechanistic and naturalistic theory of mind and consciousness. The book is meant for the researchers who are engaged in the study of consciousness and for those who are interested in philosophy of mind in general. This book will serve the purpose of the much needed counter perspective to the contemporary theories of mind working broadly within the materialist traditions.
Keywords: Philosophy of mind; Metaphysics; Philosophy of Mind; Metaphysics